2022
DOI: 10.1021/acs.jpclett.2c03449
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Kinetics Accounting for Antithermal Quenching of Luminescence in Sc2(MoO4)3: Yb/Er: Perspective beyond Negative Thermal Expansion

Abstract: Defects are common in inorganic materials and not static upon annealing of the heat effect. Antithermal quenching of luminescence in phosphors may be ascribed to the migration of defects and/or ions, which has not been well-studied. Herein, we investigate the antithermal quenching mechanism of upconversion luminescence in Sc2(MoO4)3: 9%Yb1%Er with negative thermal expansion via a fresh perspective on thermodynamics and kinetics, concerning the thermally activated movement of defects and/or ions. Our results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Ye et al indicated that the thermally activated movement of defects and/or ions in the host contributed to a change in ET efficiency. 41 Huang et al also reported that the luminescence intensity of phosphor was influenced by the formation and amount of Frenkel defects at high temperatures. 24 They described the formation of the Frenkel defect based on the deviation of the partial WO 4 group is apt to deviate from the intrinsic to the interstitial site when the temperature increases.…”
Section: Dalton Transactions Papermentioning
confidence: 97%
“…Ye et al indicated that the thermally activated movement of defects and/or ions in the host contributed to a change in ET efficiency. 41 Huang et al also reported that the luminescence intensity of phosphor was influenced by the formation and amount of Frenkel defects at high temperatures. 24 They described the formation of the Frenkel defect based on the deviation of the partial WO 4 group is apt to deviate from the intrinsic to the interstitial site when the temperature increases.…”
Section: Dalton Transactions Papermentioning
confidence: 97%